Strategies in Promoting Research Culture in SUCs and Countryside Development - Mani, Merian; Sespene, Jeter; Fetalvero, Eddie (Romblon State University Research Journal, 2011)
The Research, Extension and Production Center of Romblon State University employed strategic solutions to create a research climate, foster research interests and confidence and sustain the enthusiasm of faculty members through varied research capability building seminar workshops (RCBSW) and paper presentations. The conduct of mandatory RCBSW in the University increased substantially the number of active researchers and upgraded the performance of the faculty members and the University as a whole. The interventions made by the Southern Tagalog Agriculture and Resources Research and Development Consortium, Philippine Association of Research Managers, Inc. (PHILARM) and Commission on Higher Education – University of the Philippines, Los Banos, Zonal Research Center (CHED-UPLBZRC) have played great roles in research culture development. The series of collaborative RCBSW served as the groundwork in setting the directions and prioritizing the programs of the University. It also helped the University in defining its course of actions and in formulating annual performance targets for Research and Development. Institutional initiatives were fully implemented. Policies and guidelines on benefits, opportunities and grants were realized. Research linkages and networks were forged with local and international entities. Research climate was established and sustained. Research outputs were presented, published, disseminated and adopted, some were commercialized. Local government units facilitated the adoption of technologies in the countryside. Private entrepreneurs were also benefited from the technologies generated.